Analisis konten Keterampilan Proses Sains Dasar dalam Rencana Pelaksanaan Pembelajaran di Sekolah Dasar - Akhmad Rizki Saputra; Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri (Universitas Sebelas Maret, 2023)
This research was conducted with the aim of analyzing the content of basic science process skills in the lesson plan of learning at SD Negeri Tegalrejo No.98 Surakarta. The research was conducted using a qualitative approach. Data collection techniques in this study used document studies and interviews. This research data is in the form of content contained in the lesson plan. The validity of the instrument used is the Gregory validity test or expert validity calculations which produce valid data with increased persistence and theoretical triangulation. The results of the analysis of lesson plans the fourth grade students SD Negeri Tegalrejo No.98 Surakarta conclude that there is content related to basic science process skills in the lesson plan of learning by involving students but it is not optimal and still needs improvement. The content analysis of basic science process skills in the lesson plan was found as much as 51% contained in the communication indicator as the largest number with 38 content and stated in the sufficient category. The indicator with the second number, namely observing has a percentage of 24% or as many as 18 content with low categories. The content of basic science process skills in the third order is found in the predictive indicator as much as 11% with 8 content categorized as very low. Furthermore, the indicator grouping is in fourth place as much as 9% with 7 content that is categorized as very low. The fifth order is the indicator concludes with a percentage of 5% with 4 content categorized as very low. Meanwhile, the basic science process skills measuring indicators in the fourth grade lesson plan were not found at all. So that the total content of basic science process skills found in the lesson plan is 75 content.